2022
DOI: 10.51253/pafmj.v71i6.7223
|View full text |Cite
|
Sign up to set email alerts
|

Colistin Agar; Evaluation of a Novel Diagnostic Approach to Detection of Colistin Resistance

Abstract: Objective: To determine the diagnostic accuracy of Colistin agar for detection of Colistin resistance in clinical isolates of MultiDrug Resistant Gram-Negative Bacilli. Study Design: Cross-sectional validation study. Place and Duration of Study: Department of Microbiology, Armed Forces Institute of Pathology, Rawalpindi Pakistan, from Feb to Aug 2019. Methodology: A total of 100 Multi-Drug Resistant Gram-Negative Bacilli in clinical isolates were included. Isolates were identified using Gram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(19 reference statements)
1
2
0
Order By: Relevance
“…Although the specificity recorded in this study and that of Osei Sekyere et al (at 66,67%) agree, two other studies recorded a significantly higher specificity of ≥ 97% [11,22,23].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Although the specificity recorded in this study and that of Osei Sekyere et al (at 66,67%) agree, two other studies recorded a significantly higher specificity of ≥ 97% [11,22,23].…”
Section: Discussionsupporting
confidence: 64%
“…These discrepancies could be attributed to the different bacterial inoculum concentrations used. Ali et al demonstrated that when a 0.5 McFarland standard inoculum was used, colistinsusceptible isolates were able to grow on the media [23], whereas the same isolates were inhibited when the inoculum was diluted to a density of 1×10 ହ CFU/mL. Therefore, the high rate of MEs in this present study could be due to the inoculum used being a 0.5 McFarland standard (1.5×10 ଼ CFU).…”
Section: Discussionmentioning
confidence: 68%
“…In a study conducted by Ali and his team in Pakistan, they recommended that Colistin agar can be employed routinely as a credible method for the identification of Colistin resistance for early medication and infection control in small laboratories where BMD and genetic sequencing are not available, as well as those with a high workload (24) . Additionally, CAT is relatively easier to execute than CBDE because up to ten isolates can be inoculated per dilution plate.…”
Section: Discussionmentioning
confidence: 99%